2000
DOI: 10.14712/18059694.2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Blood and Crystalloid Cardioplegia in Patients with Left Ventricular Dysfunction Undergoing Coronary Surgery

Abstract: This study was done to compare the protective effect of blood and crystalloid cardioplegia in patients with left ventricular dysfunction undergoing coronary artery bypass grafting (CABG). Sixty consecutive patients with left ventricular ejection fraction < 35 % scheduled for CABG with the use of cardiopulmonary bypass without additional procedures were randomly divided into two groups. In the first group we used cold blood cardioplegia, in the second group cold crystalloid cardioplegia, both delivered only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Markers of myocardial damage were also not given in that study. Although a few clinical studies have reported a favorable effect of blood cardioplegia, [15][16][17][18] others have not been able to demonstrate any difference, 7,[19][20][21][22] and in some a worse outcome for patients receiving cold blood cardioplegia has been reported. 23 In our opinion the optimal group of patients to demonstrate a potential benefit for blood over crystalloid cardioplegia would be patients undergoing cardiac surgery with relatively long crossclamp times, with no compromised coronary flow to ensure the full effect of the cardioplegic solution, and with a disease susceptible to ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…Markers of myocardial damage were also not given in that study. Although a few clinical studies have reported a favorable effect of blood cardioplegia, [15][16][17][18] others have not been able to demonstrate any difference, 7,[19][20][21][22] and in some a worse outcome for patients receiving cold blood cardioplegia has been reported. 23 In our opinion the optimal group of patients to demonstrate a potential benefit for blood over crystalloid cardioplegia would be patients undergoing cardiac surgery with relatively long crossclamp times, with no compromised coronary flow to ensure the full effect of the cardioplegic solution, and with a disease susceptible to ischemia.…”
Section: Discussionmentioning
confidence: 98%